ANALISIS KEWENANGAN PEMERINTAH PUSAT TERHADAP EVALUASI DAN PEMBATALAN PERATURAN DAERAH PASCA-PUTUSAN MAHKAMAH KONSTITUSI - Alfin Suci Saputra (PT. Hasba Edukasi Mandiri, 2026)
The Constitutional Court Decisions Number 137/PUU-XIII/2015 and 138/PUU-XIII/2015 have fundamentally transformed the mechanism for evaluating and annulling Regional Regulations (Perda) in Indonesia. Prior to these decisions, the Central Government—through the Ministry of Home Affairs and the Governor as the Central Government's representative—held broad executive authority to annul Regional Regulations deemed contrary to higher regulations or public interest. Following the Constitutional Court rulings, this annulment authority was exclusively transferred to the Supreme Court through the judicial review mechanism. This study examines the juridical implications of this shift in authority on the decentralization system, central-regional relationships, and the effectiveness of Perda oversight. The research employs normative juridical methods with statutory, conceptual, and case-study approaches. The findings indicate that while the Constitutional Court decisions strengthen the principles of regional autonomy and legal certainty, this transition creates an oversight vacuum that may allow problematic regional regulations to remain in force longer. Comprehensive regulatory reform is required to address this legal gap while maintaining the balance between regional autonomy and national legal supremacy.